2017
DOI: 10.1111/ecog.03234
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal heterogeneity in climate change limits species' dispersal capabilities and adaptive potential

Abstract: Global climate change has already caused local declines and extinctions. These losses are generally thought to occur because climate change is progressing too rapidly for populations to keep pace. Based on this hypothesis, numerous predictive frameworks have been developed to project future range shifts and changes in population dynamics resulting from global climate change. However, recent empirical work has demonstrated that seasonally asynchronous climate change regimes -when a region is warming during some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 112 publications
2
28
0
Order By: Relevance
“…Lehikoinen et al (2019: figure 3) found a similar tendency to less change in arrival dates after the late 1990s. The similarity in their rate of change and that noted in our study may indicate that certain species are approaching a limitation of the ability of their arrival dates to advance further (Senner et al 2018). in early spring migrants such advancement may be constrained by cold, wet spring weather (Holroyd and Beaubien 1997a, b).…”
Section: Discussionsupporting
confidence: 69%
“…Lehikoinen et al (2019: figure 3) found a similar tendency to less change in arrival dates after the late 1990s. The similarity in their rate of change and that noted in our study may indicate that certain species are approaching a limitation of the ability of their arrival dates to advance further (Senner et al 2018). in early spring migrants such advancement may be constrained by cold, wet spring weather (Holroyd and Beaubien 1997a, b).…”
Section: Discussionsupporting
confidence: 69%
“…Instead, our results add to the growing literature suggesting that there are common ecological principles, such as the occurrence of contrasting climate change regimes, that determine the severity of phenological mismatches across sites and species (Visser and Both , Senner et al. ).…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, we have little understanding of the spatial variation in the frequency and strength of mismatches (Senner et al. ), even though the rate of climatic change is inconsistent across both latitudes and biomes (Loarie et al. , Burrows et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, variability among species is wide and poorly understood, and the mechanisms underlying these changes need further study (Knudsen et al 2011). Furthermore, seasonally asynchronous climate change-when a region warms during some parts of the year then cools in others-may constrain species' responses to climate change (Senner et al 2018).…”
Section: Earlier Spring Arrival Of the Mountain Bluebird In Central Amentioning
confidence: 99%